Private Higher Education Intention in Adopting Blockchain Technology on Accounting Information System (AIS) (Universitas Muhammadiyah Yogyakarta, 2024)
Research aims: This study was conducted with the aim of testing and obtaining empirical evidence regarding the intention of private higher education institutions (HEIs) to adopt blockchain in accounting information systems (AIS) using the unified theory of acceptance and use of technology (UTAUT) model. Design/Methodology/Approach: The sample of this research is private HEIs in Java that have been accredited